EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KOTA TIDORE KEPULAUAN - Daud, Rahmatia M; Sondakh, Jullie J.; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Local revenue (PAD) is an important indicator that is considered as the level of independence of local governments in managing their regional finances. In order to increase the local revenue, the local government must be biased in obtaining sources that can generate income in its area which is potential for taxes and levies. The purpose of this study, to determine the effectiveness and contribution to the Original Revenue in Manado City. The analytical method used is descriptive qualitative, namely analyzing the level of effectiveness and contribution of the hotel tax realization data in the Manado City. The results showed that the effectiveness of Hotel Tax in 2013 until 2017 increased. The highest effectiveness is in 2017 with a percentage of 127.51% and is included in very effective criteria, and the Hotel Tax Contribution from 2013 to 2017 goes into very few criteria. Unfortunately on 2019 it decreased to 94,81%. And that included in the lowest criterion number is in 2015 with a percentage of 6.28%. It because there is still a lack of awareness of taxpayers in paying taxes. We can see the ascent took place in the years 2018-2019 where the hotel tax contributed quite well with a percentage of 10.39% (2018) and 10.29% in 2019. Therefore, there is a need for socialization or seminar for taxpayers. If it is still infringing, it should be penalized for taxpayers who are late paying taxes.